STATISTICAL STUDY ON THE PERCEPTION OF STUDENTS WEARING FIXED ORTHODONTIC APPLIANCES ON PERIODONTAL CHANGES - Mahmoud Katta; Petre Costin Mărășescu; Felicia Ileana Mărășescu; Ioan Ovidiu Gheorghe; Mihaela Jana Țuculină; Hazem Abbas; Cristian Levente Giuroiu; Andreea Mariana Bănățeanu; Oana Amza; Ionela Teodora Dascălu (Romanian Journal of Oral Rehabilitation)
The aim of the study is to evaluate students who carry fixed metal orthodontic appliances based on a questionnaire that contained 16 questions, including, methods of ensuring oral hygiene and their influence on periodontal changes that may occur during orthodontic treatment. The questionnaire was conducted using the Google Forms platform. For statistical purposes, the Chi squared test was applied. Most gingival bleeding occurred in students with fixed orthodontic appliances of the 18-22 year age group. It was found that most gingival bleeding was found in students with fixed braces using manual toothbrush. Mouthwash was the most widely used auxiliary means of hygiene. The oral shower was the least auxiliary hygiene used. The use of interdental toothbrush as an additional method of ensuring dental hygiene in carriers of orthodontic appliances has been associated with a reduced frequency of gingival bleeding. Most students with fixed braces have allocated between 3-5 minutes of tooth brushing. A large percentage of students with fixed braces reported difficulty chewing.